A qualitative examination of the sport music preferences of NCAA Division I athletes - Ryan, Z.; Czech, D. R.; Harris, B. S.; Todd, S.; Biber, D. D. (International Journal of Sports Science, 2016)
The purpose of the current study was to examine the sport music preferences (SMP) of NCAA Division I athletes. A secondary purpose was to examine SMP from a gender and contact sport type (collision, contact, limited-contact) perspective. Participants (n = 21) were male and female NCAA Division I athletes from a southeastern university. The consensual qualitative research (CQR) protocol was used to analyze the data pertaining to the music athletes prefer to listen to prior to participating in their sport. The results suggest that, overall; athletes prefer music that is fast and upbeat, pay more attention to the beat than the lyrics, and like rap and/or hip-hop music. Female and limited-contact sport athletes also reported listening to multiple genres of music, while male and collision sport athletes pay attention to the lyrics in select songs. Outcomes of the research and future research suggestions is discussed.